SISTEM PEMETAAN RUMAH IBADAH PROVINSI BALI BERBASIS GOOGLE MAPS PADA KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI BALI - I Gusti Ngurah Winanda Wijaksana (LPPM STMIK STIKOM Indonesia, 2020)
The management of information on houses of worship is a part of the management of Education, Religion and Religious informations which is managed at the Regional Office of the Ministry of Religion in Bali. In practice, houses of worship data collected and processed manually with Microsoft Excel application and the information has been given to the community is just the number of houses of worship in every regency or city in Bali. While the public wants more detailed information of houses of worship including the address and location on a map. Bali House of Worship Mapping System is able to provide information of houses of worship in Bali from six religions that have been recognized in Indonesia including location information on Google maps and video documentation on YouTube. So, people can easily search all the houses of worship informations in Bali using web browser.